Analisis Persepsi Mahasiswa terhadap Efektivitas Metode Evaluasi pada Mata Kuliah Teknik Reportase dan Wawancara dalam Proses Pembelajaran - Trisnawati Bura; Maria Palma Vita; Rabita Isnanda; Fatimatul Jahro; Albertino Rosdina Pero (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2025)
This study aims to analyze student perceptions of the effectiveness of evaluation methods used by lecturers in the Reportage and Interview Techniques course in the learning process. Evaluation methods have a crucial role in measuring students' understanding and skills, as well as providing constructive feedback to improve the quality of learning. However, its effectiveness is highly dependent on how the method is perceived by students as the main subject of learning. This research uses a quantitative approach by distributing questionnaires to students who have taken the Reportage and Interview Techniques course. The data collected will be analyzed descriptively to identify the level of satisfaction, relevance, fairness, and impact of evaluation methods on student learning motivation. The results of the study are expected to provide a comprehensive picture of the strengths and weaknesses of the evaluation methods applied, as well as valuable input for lecturers in developing evaluation strategies that are more effective and in accordance with the needs and characteristics of students. The findings are also expected to contribute to improving the overall quality of the learning process in the Reportage and Interview Techniques course.